Empirical Study of the Impact of Work From Home (WFH) Policy and Top Management Support on Employee Performance - Leni Mardianah; Syamsul Hidayat; Hamidah (Kusuma Negara Business School, 2020)
This study aims to examine and analyze the direct effect of Work from Home (WFH) and Superiors' Support on Employee Performance. This study also examines and analyzes the indirect effect of Work from Home (WFH) on Employee Performance with Superior Support as a mediating variable. The sample in this study were ASN employees of the Ministry of Public Works and Public Housing, Directorate of Highways, PJN 1 West Java, who implemented the Work Form Home policy. The number of respondents who participated in this study were 60 respondents. The method and analysis tool are the Partial Least Square (PLS) - Structural Equation Model (SEM) to test the hypothesis. The results of this study indicate that work from home has a significant effect on superiors' support, work from home has a significant effect on employee performance, superiors' support has no significant effect on employee performance and superiors' support cannot mediate the relationship between work from home and employee performance. Further discussed in this study.